2020
DOI: 10.1002/jbt.22541
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin, the dipeptidyl peptidase‐4 enzyme inhibitor, lessens CHOP and GRP78 biomarkers levels in cisplatin‐induced neurobehavioral deficits: A possible restorative gateway

Abstract: Cisplatin (CP) is a cornerstone chemotherapeutic agent, however, its neurotoxicity is a chief cause of its limited usage. Linagliptin, which is a dipeptidyl peptidase‐4 enzyme inhibitor, has exhibited considerable neuroprotective potential. We aimed to evaluate the linagliptin modulatory effects on endoplasmic reticulum (ER) stress, redox status, and apoptosis in CP‐induced neurotoxicity. Thirty mice were allocated equally into the control group, Group II: CP group, and Group III: linagliptin treated CP group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…We found that LNG down-regulated caspase-3 expression and showed antiapoptotic effects, confirming previous studies. Previously it has been reported that LNG has a marked neuroprotective, anti-apoptotic and cognitive improving properties in in-vitro cerebral ischemia model [27].…”
Section: Discussionmentioning
confidence: 99%
“…We found that LNG down-regulated caspase-3 expression and showed antiapoptotic effects, confirming previous studies. Previously it has been reported that LNG has a marked neuroprotective, anti-apoptotic and cognitive improving properties in in-vitro cerebral ischemia model [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several cytotoxic compounds including cisplatin may facilitate impairment of LTP. Cisplatin-induced cognitive impairment was documented in animals models using Morris water maze [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Y-maze test [ 33 , 41 , 42 , 43 , 44 ], T-maze [ 45 , 46 , 47 ], and novel object recognition test [ 9 , 48 , 49 , 50 , 51 ], including in humans in the treatment of oncological diseases using chemotherapy using cisplatin as a chemostatic [ 12 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (CDDP) is one of the leading anticancer agents in cancer chemotherapy. The consistent worry of clinicians about cisplatin use is the variegated side effects chiefly linked with neurotoxicity, nephrotoxicity, and testicular 7,23,24 However, studies probing into the mechanisms of CDDP toxicity show that a network of oxidative stress, pro-inflammation and redox-mediated apoptosis play a pivotal role. 25 Emerging research reports have revealed increasing interest for exploration of natural products to combat the integrated mechanism underlying the severe side effects of CDDP.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 31 Cisplatin is clinically known to cause structural CNS mutilations which correlate with the cognitive deficits observed in CDDP‐treated patient. 23 Therefore, our study examined CICI and behavior of rats after CDDP injection via MWM and Y maze tests. Morris water-maze test is a very common behavioral model to test rodent spatial memory and learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation